Integrasi Etika AI dalam Pendidikan Agama Kristen: Tantangan dan Peluang - Nenomataus, Ade Epatri; Rantung, Djoys Anneke; Naibaho, Lamhot (LPPM Institut Pendidikan Nusantara Global, 2024)
AI ethics is a branch of ethics that focuses on moral principles in the development and use of AI technologies. This research aims to integrate AI ethics in Christian religious education and explore the opportunities and challenges in the process, as well as strategies to overcome these challenges. The method used is a descriptive qualitative approach with literature studies from various sources such as books, national and international journals, and websites. The results show the importance of integrating AI ethics in Christian religious education to shape students' characters, prepare their future, and improve the quality of learning. Challenges faced include limited resources, digital divide, lack of understanding of AI ethics, and the need for adequate supervision and regulation. Strategies to address these challenges include improving technological infrastructure, training for teachers, and developing policies that support the integration of AI ethics in Christian religious education.